Energy Management in Colombia: Evolution and Prospects for the Sustainable Transition (1993-2023) - Juan Camilo Cardona CASTAÑO (International Journal of Environmental, Sustainability, and Social Science, 2025)
Colombia is seeking to transition to alternative energy and move towards a sustainable future. The purpose of this study was to analyze Colombia's energy management from 1993 to 2023, with the goal of establishing projection scenarios for 2030. To achieve this objective, we reviewed energy data from institutional databases at the Ministry of Mines and Energy, conducted a hemerographic analysis, and applied inferential statistics through linear regression to examine the behavior of the analyzed period. The method used is Case study, Scale and periodicity of analysis 1993-2023. Over the past three decades, comprehensive infrastructure has been developed to increase energy levels and electricity capacity for alternative energy production throughout the country. Our findings suggest that Colombia's energy sector may stabilize by 2030, but environmental pressures such as climate change, deforestation, and other factors could negatively impact the country's energy matrix. The design and implementation of Colombia's energy transition policy have faced obstacles. Ultimately, it is essential to advance towards a sustainable energy transition in Colombia, considering environmental challenges and transforming the energy matrix towards renewable energies.